2011
DOI: 10.1186/1746-6148-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Reported analgesic administration to rabbits undergoing experimental surgical procedures

Abstract: BackgroundIt has become widely accepted that whenever animals are used in scientific procedures, the 3Rs principle of replacement, reduction and refinement described by William Russell and Rex Burch should be adhered to. Animals should be replaced with non-sentient alternatives if possible, the number of animals used should be reduced and experimental procedures should be refined to minimise pain, suffering and distress. Administration of analgesic agents to animals undergoing surgical procedures is a refineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…These inconsistencies have the potential to impact research results as well as the welfare of the animals. However, typically this information is not included in the methods sections of papers that arise from the work, as has been reported in studies that aimed to quantify the prevalence of analgesic administration [ 6 , 7 , 8 , 9 ]. Use of standardized checklists for reporting methodological details of animal-based research may assist in standardizing this information and decreasing inconsistencies in practice [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistencies have the potential to impact research results as well as the welfare of the animals. However, typically this information is not included in the methods sections of papers that arise from the work, as has been reported in studies that aimed to quantify the prevalence of analgesic administration [ 6 , 7 , 8 , 9 ]. Use of standardized checklists for reporting methodological details of animal-based research may assist in standardizing this information and decreasing inconsistencies in practice [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have aimed to quantify the prevalence of analgesic administration following surgery and/or other potentially painful procedures in a variety of laboratory animal species [ 6 , 7 , 8 , 9 ]. The studies concluded that the use of analgesia has increased over time, but the proportion of animals reported as receiving analgesics remains less than the proportion subjected to painful procedures, especially in the case of smaller species [ 6 , 7 , 8 , 9 ]. Similarly, a Canadian survey of analgesia-withholding found that over 12 months, 42,700 animals (approximately 1.9% of total national use) were used in invasive protocols that received animal ethics committee (AEC) approval to withhold analgesia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, such assurance is probably misplaced. Coulter and colleagues 31 found that papers reporting ethical approval were also more likely to report systemic analgesic administration than those that did not. Furthermore, standards of ethical review differ widely between countries.…”
Section: Discussionmentioning
confidence: 99%
“…The problems with this approach are described elsewhere, and the effect of exclusion is contentious. 45 46 Previous studies comparing the frequency of reported analgesic use in rodents (10-20%, Stokes and colleagues), 18 larger laboratory animals, including pigs (67%, Coulter and colleagues), 30 and rabbits (16-50%, Coulter and colleagues) 31 over two time periods have elucidated trends in the refinement of animal experiments. However, the present review revealed problems with using the level of reported analgesic use to quantify refinement.…”
Section: Discussionmentioning
confidence: 99%
“…The Use of Experimental Refinements in Practice Several structured and systematic literature reviews have given some insight on certain experimental refinements, notably, killing methods (Pound and Nicol, 2018;Uhlig et al, 2015) and the use of anesthetics and analgesics (Bertrand, Sandersen and Flecknell, 2018;Carbone and Austin, 2016;Coulter, Flecknell and Richardson 2009;Coulter et al, 2011;Pound and Nicol, 2018;Richardson, and Flecknell, 2005;Stokes, Flecknell and Richardson, 2009;Uhlig et al, 2015). For example, animal research involving surgical procedures carried out on diverse species and published in peer-reviewed journals has been analyzed with regard to analgesic and anesthetic administration (Coulter et al, 2011;Coulter, Flecknell and Richardson, 2009;Richardson and Flecknell, 2005). Stokes, focused on studies conducted in two time periods (2000-2001 and 2005-2006), assessing trends in the administration of analgesics and anesthetics to laboratory mice and rats undergoing surgical procedures.…”
Section: 1mentioning
confidence: 99%